Inflation Expectations in the EU: Results from Survey Data - Hannah Nielsen (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 2003)
Inflation expectations are extracted from the Consumer Survey, which is conducted by the European Commission for the European Union. Using the probability method to quantify the qualitative answers different distribution functions and scaling parameters are assumed to cope with the properties of the data properly. The forecasting ability of respective series is assessed also compared to the balance statistic. Furthermore the time horizon of the survey participants while answering the questionnaire is analyzed, because the empirical results show that it might not coincide with the time horizon implied by the formulation of the question.
urn:nbn:de:kobv:11-10049942
Keywords: C22; E58; C42; E37; 330; Inflation expectations; survey data; quantification methods; Inflationserwartung; Konsumklima; Schätzung; EU-Staaten